PENGARUH FINANCIAL DISTRESS, OPINI AUDIT, DAN PERGANTIAN MANAJEMEN TERHADAP AUDITOR SWITCHING - Octarisa, Maida Zerlina; Syamsuri, Syamsuri (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to determine the effect of Financial Distress, Audit Opinion, and Management Change on Auditor Switching in companies listed on the Indonesia Stock Exchange (BEI) for the period 2018-2022. Based on the purposive sampling method, a sample of 35 companies was obtained. The analysis method used is descriptive statistical method using logistic regression analysis tool. Hypothesis testing was conducted using Eviews 12 software. The results of this study indicate that Financial Distress has no effect on Auditor Switching, Audit Opinion has a significant effect on Auditor Switching. Management Change has no effect on Auditor Switching